Free WiFi to monitor flow in Hanoian traditional markets anonimized and aggregated dataset made open access - CGIAR Platform for Big Data in Agriculture (2021)
We have made available fully open access the is the aggregation of more than 100 millions smartphones occurrences over a period of 1.5 year monitoring 5 Hanoian markets before and during the first COVID19 outbreak. The dataset is fully documented (metadata), registered (DOI:10.5281/zenodo.5707312) and findable in a major datasets database.